Solid phase microextraction (SPME) fibers: In situ measurements of endocrine disrupting chemicals in seawater - Santos, Dayana M. [UNESP]; Williams, Mike; Kookana, Rai; De Marchi, Mary R. R. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2018)
A study involving microextraction fibers was carried focusing on calibration setup for endocrine disrupting chemicals (EDCs) sorption in seawater. The sorption of EDCs (triclosan (TCS), bisphenol A (BPA) and 17α-ethinylestradiol (EE2)) were checked using acrylate, nylon and polydimethylsiloxane (PDMS) fiber coating with 5 and 1 cm length after 7 days of exposure. Extracts were determined by liquid chromatography tandem mass spectrometry (LC-MS/MS). Comparing with previous studies, results indicate a promising use of this device for field monitoring as well as for bioavailability studies mimicking the organism uptake from environment.
Keywords: Acrylate fiber; Endocrine disrupting chemicals; Passive sampler; Seawater